Anomalous electron heating effects on the E region ionosphere in TIEGCM. Issue 6 (19th March 2016) - Liu, Jing; Wang, Wenbin; Oppenheim, Meers; Dimant, Yakov; Wiltberger, Michael; Merkin, Slava
Abstract: We have recently implemented a new module that includes both the anomalous electron heating and the electron‐neutral cooling rate correction associated with the Farley‐Buneman Instability (FBI) in the thermosphere‐ionosphere electrodynamics global circulation model (TIEGCM). This implementation provides, for the first time, a modeling capability to describe macroscopic effects of the FBI on the ionosphere and thermosphere in the context of a first‐principle, self‐consistent model. The added heating sources primarily operate between 100 and 130 km altitude, and their magnitudes often exceed auroral precipitation heating in the TIEGCM. The induced changes in E region electron temperature in the auroral oval and polar cap by the FBI are remarkable with a maximum Te approaching 2200 K. This is about 4 times larger than the TIEGCM run without FBI heating. This investigation demonstrates how researchers can add the important effects of the FBI to magnetosphere‐ionosphere‐thermosphere models and simulators. Key Points: A new module associated with the Farley‐Buneman Instability has been implemented in the TIEGCM Maximum E region Te enhancement is close to 2200 K Electron temperature enhancement is proportional to the strengths of electric fields